Relationship Five Behavioral Indicators and Healthy Living with Tuberculosis Multidrug-Resistant - Heri Mulyanto (Universitas Airlangga, 2014)
Clean and healthy live behavior is closely related to the emergence of infectious diseases, including the continuation of Tuberculosis (TB) to Multidrug Resistance Tuberculosis (MDR-TB). This study is intended to determine the relationship between the 5 indicators of clean and healthy living behavior with MDR-TB in Dr. Saiful Anwar Malang Hospital. The study was conducted using a retrospective analytic design with a case-control study design. Subjects were drawn from the population using simple random sampling with a ratio of 1: 1 between cases and controls, MDR-TB patients in the MDR-TB clinic as many as 27 patients as a case group and patients who had TB treatment for at least 6 months with the results of negative acid-resistant bacteria as much as 27 patients as a control group. The variables in this study are clean and healthy living behavior, demographic variables, and MDR-TB. The results of the study were calculated using the Chi-square test with a confidence level of 95% (α = 0.05) indicating age, sex, education level, and marital status as well as the behavior of preventing additional infections not related to MDR-TB. Nutrient consuming behavior (OR = 0.25; p = 0.014), exercise behavior (physical activity) (OR = 0.16; p = 0.00), behavior using health care facilities (OR = 0.091; p = 0, 01), and the behavior of providing a healthy home environment (OR = 0.28; p = 0.03) are related to the incidence of MDR-TB. There are four variables of clean and healthy living behavior that are associated with MDR-TB so that health service facilities are advised to provide promotion of clean and healthy behavior for TB patients so that they do not continue to become MDR-TB.